Campomanesia genus – a literature review of nonvolatile secondary metabolites, phytochemistry, popular use, biological activities, and toxicology - Duarte, Luiza de Souza; Pereira, Mariana Toledo Martins; Pascoal, Vinicius D’Ávila Bitencourt; Pascoal, Aislan Cristina Rheder Fagundes (Eclética Química, 2020)
The genus Campomanesia belongs to the Myrtaceae family and has about 30 species. It is characterized by citrus-flavored fruits. Several articles describe the extensive use of its fruit, such as in the food industry, however, other parts of the plants are also used for food or pharmacological purposes such as the leaves, flowers, seeds, and roots. Analyzing works published on the genus in the period 2005-2019, we observed that the classes of main flavonoid compounds present are anthocyanins, chalcones, coumarins, tannins, and saponins. Species of this genus are also used as a medicine in the treatment of wounds, toothaches, fractures, and bruises. Therapeutic activities have also been detected for Campomanesia, such as antimicrobial, antiulcerogenic, antiprotozoal, anti-inflammatory, and antidiarrheal activity, antiproliferative and antioxidant potential, antiplatelet, antithrombotic, and fibrinolytic activities, as well as hypotensive effects. There are a small number of works demonstrating the low toxic potential of plant extracts. Thus, the Campomanesia genus presents pharmacological potential to be explored.